Response of germination and seedling growth to soil particle size of three herbaceous perennials on alpine zone of Mt. Fuji - Anisuzzaman, G. M.; Suzuki, Hiroshi; Kibe, Takeshi; Masuzawa, Takehiro (National Institute of Polar Research, 2001)
P(論文) Polygonum cuspidatum, P. weyrichii and Artemisia pedunculosa are herbaceous perennials in the alpine zone on Mt. Fuji. The effect of soil particle size on seed germination and seedling growth of these species was investigated. In the experiment three different particle size soils (large particle size LPS, medium particle size MPS, and small particle size SPS) were used. The other experiment was designed under three different watering intervals (every day, every two days, and every four days). Soil particle size had a great impact on seed germination and seedling growth. The highest percentage of seeds germinated in SPS and lowest in LPS soil, irrespective of the species. In the case of A. pedunculosa there was no significant difference of seed germination between SPS and MPS soils. However, the other two species had significantly reduced percentages of seed germination with increasing soil particle size. The maximum root length of seedlings was significantly longer in LPS and MPS compared to the SPS soil group, for all species. The number of root tips was increased with decreasing soil particle size, irrespective of the species. Further, larger aboveground biomass was found in seedlings of SPS than those of LPS and MPS. A. pedunculosa showed a slightly different pattern of seed germination and seedling growth compared to the two Polygonum species. Seed germination of A. pedunculosa was comparatively independent of soil particle size, and it may have conservative water use strategy. On the other hand, seed germination of Polygonum species was highly affected by the soil particle size, and those species may adapt to the water deficit condition by taking up water from deeper soil. departmental bulletin paper